2022
DOI: 10.1186/s12885-022-09186-z
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4–201 transcript as a putative biomarker in colorectal cancer

Abstract: Background Transcripts with alternative 5′-untranslated regions (UTRs) result from the activity of alternative promoters and they can determine gene expression by influencing its stability and translational efficiency, thus executing complex regulation of developmental, physiological and pathological processes. Transcriptional regulation of human SMAD4, a key tumor suppressor deregulated in most gastrointestinal cancers, entails four alternative promoters. These promoters and alternative transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In the PPI network, the following eight core proteins were identified: SMAD4, HIF-1A, CDKN1B, CDK6, FOXO3, CTNNB1, KRAS, and NRAS. SMAD4 is a member of the SMAD family of encoded signal transduction proteins that are essential for maintaining tissue homeostasis and cell cycle regulation [35,36]. Amini et al [37] found that SMAD4 expression increased after IS, especially in those with the GG allele rs975903.…”
Section: Plos Onementioning
confidence: 99%
“…In the PPI network, the following eight core proteins were identified: SMAD4, HIF-1A, CDKN1B, CDK6, FOXO3, CTNNB1, KRAS, and NRAS. SMAD4 is a member of the SMAD family of encoded signal transduction proteins that are essential for maintaining tissue homeostasis and cell cycle regulation [35,36]. Amini et al [37] found that SMAD4 expression increased after IS, especially in those with the GG allele rs975903.…”
Section: Plos Onementioning
confidence: 99%
“…[3][4][5] SMAD Family Member 4 (SMAD4) is the core signalling transduction molecule in the transforming growth factorβ (TGF-β) signalling pathway. Loss of SMAD4 occurs in about 30% in CRC cases, 6 and its deficiency increases the risk of recurrence and poor prognosis of CRC patients. SMAD4 has two major structural domains, MH1, which binds to DNA, and MH2, which interacts with MH1 for transcriptional regulatory activity.…”
Section: Introductionmentioning
confidence: 99%